Woody Species Structure and Regeneration Status in Kafta Sheraro National Park Dry Forest, Tigray Region, Ethiopia - Fitsum Temesgen; Bikila Warkineh (International Journal of Forestry Research)
The study was conducted in Kafta Sheraro National Park (KSNP) dry woodland natural forest located in Kafta Humera and Tahitay Adiyabo weredas (districts), Western and Northwestern Zones of Tigray regional governmental state, North Ethiopia. The objective of the study was to explore the floristic composition, structure, and regeneration of woody species in the home of Loxodonta africana L., Hippotragus equinus, Anthropoides virgo, Ourebia ourebi, Crocuta crocuta, Tragelaphus strepsiceros, Phacochoerus africanus, and unidentified crocodile and fish species. In the park, the vegetation ecology has not been studied up to date which is necessary for conservation. The systematic sampling technique was used to collect vegetation and human disturbance (presence and absence) data from August to December 2018. The vegetation data were collected from 161 plots each with a size of 400 m2 (20 m × 20 m) for tree/shrub while subplots of size 100 m2 (10 m × 10 m) and 25 m2 (5 m × 5 m) for sapling and seedling, respectively, were established in the main plots. Individual tree and shrub diameter at breast height (DBH) ≥2.5 cm and height ≥ 2 m were measured using tape meter and clinometer, respectively. Diameter at breast height (DBH), frequency, density, basal area, and importance value index (IVI) were used for vegetation structure description while the density of mature trees, sapling, and seedling was used for regeneration. A total of 70 woody species (46 (65.7%) trees, 18 (25.7%) shrubs, and 6 (8.6%) tree/shrub) were identified. The total basal area and density of 79.3 ± 4.6 m2·ha−1 and 466 ± 12.8 stems·ha−1, respectively, were calculated for 64 woody species. Fabaceae was the most dominant family with 16 species (22.9%) followed by Combretaceae with 8 species (11.4%). The most dominant and frequent species throughout the park were Acacia mellifera, Combretum hartmannianum, Terminalia brownii, Balanites aegyptiaca, Dichrostachys cinerea, Acacia senegal, Acacia oerfota, Boswellia papyrifera, Ziziphus spina-christi, and Anogeissus leiocarpus. Abnormal patterns of selected woody species were dominantly identified. The regenerating status of all the woody plant species was categorized as “fair” (18.75%), “poor” (7.81%), and “none” (73.44%). There was a significant correlation between altitude, anthropogenic disturbance (grazing and fire frequency), and density of seedling, sapling, and mature trees. But there was no correlation between gold mining and regeneration population. However, there is a good initiation for the conservation of the park; still, the vegetation of the park was threatened by human-induced fire following intensive farming, gold mining, and overgrazing. Therefore, the study area was the habitat for the population of the African elephant; species with low importance value indices and lack or having few seedling and sapling stage should be prioritized for conservation, and their soil seed banks should be studied further.